PREDICTION OF THE CONSEQUENCES OF FIRE AND EXPLOSION AT GAS STATIONS IN BANDA ACEH CITY USING THE ALOHA APPLICATION IN 2020 - Mauliany, Fouriza Dinda; Ariscasari, Putri; Zulkifli, Zulkifli (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2022)
The National Fire Protection Association (NFPA) reported 5,020 cases of fire at gas stations, of which 61% of gas station fires were caused by vehicle fires, 27% by technical errors, and 12% caused by other causes. In 2017 at the Simpang Jam gas stationin Banda Aceh, which caused huge losses. Previously, there had never been a study on the impact of fire and explosion risks, especially for gas stations that were close to residential areas in the city of Banda Aceh.. This research is descriptive analytic with a case study design conducted at 2 gas stations in Banda Aceh using secondary data obtained from gas stations and BMKG and then processed using ALOHA software. The results showed that the flammable area at the Batoh Gas Station was 28 yards, with a red zone (17 yards), an orange zone (21 yards), and a yellow zone (28 yards). The flammable area at the Simpang Jam gas station is 24 yards, with a red zone (13 yards), an orange zone (17 yards), and a yellow zone (24 yards). Both gas stations do not have an emergency response plan to anticipate fires and explosions at these gas stations. it is recommended to the managers of Batoh Gas Stations and Simpang Jam Gas Stations to make an emergency response plan and provide training on fire and explosions for each worker, it is hoped that the government will tighten regulations regarding land that must be vacated in hazard zones to minimize the impact of fire and explosions at these gas stations.